2021
DOI: 10.1080/23311932.2021.1916168
|View full text |Cite
|
Sign up to set email alerts
|

Study on farmers’ Pest management strategy, knowledge on pesticide safety and practice of pesticide use at Bhaktapur district, Nepal

Abstract: Nepal being an agricultural country, the majority of the population is involved in agriculture. Pests are one of the major problems in the agriculture sector. Pesticides are being widely used to encounter this problem. This study aims to determine the knowledge level of farmers on pesticides and their use. Specifically, it investigates the pest management strategy, pesticide use, and safety measures used by the farmers. For this study, four municipalities of Bhaktapur district were selected with 100 respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…This advocates higher health hazard risk among the workers. Despite knowing about the pesticides' negative health effects, the usage of preventative measures were found inadequate in the similar study of Bhaktapur (Thapa et al, 2021) and of Gaza (Yassin M et al, 2002). Poor pesticide safety and use situation in the study area is attributed to weak safety enforcement system in the study area.…”
Section: Availability and Use Of Ppementioning
confidence: 74%
See 1 more Smart Citation
“…This advocates higher health hazard risk among the workers. Despite knowing about the pesticides' negative health effects, the usage of preventative measures were found inadequate in the similar study of Bhaktapur (Thapa et al, 2021) and of Gaza (Yassin M et al, 2002). Poor pesticide safety and use situation in the study area is attributed to weak safety enforcement system in the study area.…”
Section: Availability and Use Of Ppementioning
confidence: 74%
“…Pesticides are frequently employed to overcome this problem. (Thapa et al, 2021) Properly applied, a pesticide contribute to higher yields, improves product quality and meet the demand of agriculture by controlling weeds, domestic pests, disease bug vectors, and home gardening. (Rani & et al, 2020;PPC, 2020) However, they are extremely poisonous causing serious health and environmental dangers.…”
Section: Introductionmentioning
confidence: 99%
“…Aphid was the most severe for them, followed by fruit fly, fruit borer, whitefly, and white grubs, each with index values of 0.818, 0.632, 0.544, 0.53, and 0.486 (Table 4). Insect pests are one of the factors affecting vegetable production (Thapa et al 2021). Moreover, Jha and Regmi (2009) also found that the incidence of pests has increased in commercial fields.…”
Section: Insect Pests Of Vegetablesmentioning
confidence: 99%
“…The impacts of climate change, such as increasing extreme precipitation, gradually growing temperature, and melting glaciers, have a significant effect on agricultural production, food security, terrestrial ecosystems, and the overall livelihood of the population in Nepal [4][5][6] and India [7][8][9]. In Nepal, rainfed agriculture is a primary source of food production [10] and the majority of people depend on agricultural activities for their livelihoods [11,12], which is common in the Indian Himalayan region [13]. In addition, climate change has resulted in water scarcity with more uncertain and irregular of water resources where more than two million people have lack of access to safe drinking water [14].…”
Section: Introductionmentioning
confidence: 99%